Screening of Strains of the Medicinal Mushroom Fomitopsis officinalis (vill.) Bondartsev & Singer Promising for Biotechnological Use - Mykchaylova, Oksana; Poyedinok, Natalia; Shchetinin, Valeria (Innovative Biosystems and Bioengineering, 2023)
Background. Macromycete cultivation methods development will contribute to the production of biotechnological products based on fungus. Determination of the main factors affecting medicinal macromycetes’ life processes allows to control biosynthetic activity of a fungal organism and obtain biotechnological products based on it. Objective. Screening of Fomitopsis officinalis strains promising for biotechnological use, and determining of physico-chemical factors that affect the cultures life processes. Methods. The objects of the study were three pure cultures of F. officinalis (IBK-2497, IBK-2498, IBK-5004). The influence of the acidity of the environment on the growth of mycelium, the needs of the cultures in the sources of carbon and nitrogen nutrition were determined. The following carbon sources were used: monosaccharides (glucose, xylose), disaccharides (sucrose, lactose) and trisaccharides (raffinose), polysaccharides (starch); nitrogen sources: KNO3, (NH4)2HPO4, asparagine, peptone. Dynamics of the culture growth were determined under the conditions of deep cultivation, on a liquid nutrient medium of glucose-peptone-yeast extract (GPA), g/l: glucose – 30.0; peptone – 3.5; yeast extract – 2.0; KH2PO4 – 1.0; K2HPO4 – 1.0; MgSO4×7H2O – 0.25. Results. The pH range between 5.5 and 6.0 was the most favorable for active growth of all studied strains of F. officinalis. The best carbon sources for growth were glucose and starch; peptone and asparagine were the best source of nitrogen. Nutrient media with xylose, lactose and nitrate nitrogen were least suitable for growth. Analysis of the strains growth dynamics on the GPA medium showed that the largest mass of mycelium (up to 11.54 ± 0.2 g/l) was produced by culture F. officinalis IBK-5004 on the 10-th day of cultivation. Cultures F. officinalis IBK-2497, IBK-2498 grew slower, and the mycelial mass was 10.33 ± 0.2 and 9.68 ± 0.3 g/l on the 14-th day of cultivation. Conclusions. Based on the obtained data, the F. officinalis IBK-5004 strain was selected. It can be considered a promising mycelial mass producer based on the set of characteristics.